The development of a questionnaire to assess knowledge of epilepsy: 2--Knowledge of own condition. - Jarvie, S; Espie, C; Brodie, M (1993)
In a previous paper, a questionnaire to assess general knowledge of epilepsy (E.K.P.--G) was described (same authors). In the present paper, the development of a complementary questionnaire providing a profile of the individual's knowledge of his or her own condition is described. Results from external validation, item refinement and a clinical trial suggest this measure (the Epilepsy Knowledge Profile--Personal) provides a valid and comprehensive assessment profile which has considerable practical applications.